Chemotherapy with a TP Regimen in Combination with Stereotactic Radiotherapy Could Significantly Optimize the Clinical Efficacy of NSCLC Treatment. (14th June 2022) - Wu, Chenglin; Chen, Biyu; Wang, Meifang; Tang, Yijun
Abstract : The changes in lifestyle and bad living habits have a significant impact on the health of people, resulting in an increasing prevalence of lung cancer. The most prevalent kind of lung cancer is nonsmall cell lung cancer (NSCLC), which accounts for around 80% of all cases. Chemotherapy is a common treatment method in clinical practice with certain negative effects. The primary goal of this study is to investigate the clinical efficacy of stereotactic radiotherapy in combination with a docetaxel plus cisplatin (TP) chemotherapy regimen in patients with nonsmall cell lung cancer (NSCLC) and their impact on the levels of cytokeratin fragment 21-1 (CYFRA21-1) and metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) in NSCLC patients. Eighty patients who were admitted to the hospital between November 2016 and November 2019 were recruited and assigned to receive either chemotherapy with a TP regimen (the control group) or chemotherapy with a TP regimen plus stereotactic radiotherapy (the observation group). The WHO response evaluation criteria (REC) for solid tumors were adopted to analyze short-term efficacy, and the Karnofsky performance status (KPS) score was used to assess the quality of life by recording adverse reactions in the blood system, kidney, gastrointestinal tract, bladder, nervous system, and heart. The levels of CYFRA21-1 and MALAT1 in serum before and after the treatment were determined and compared. As a result, the observation group showed higher total efficacy and MALAT1 level, better quality of life, and lower CYFRA21-1 level than the control group (P < 0.05 ). Stereotactic radiotherapy plus TP regimen chemotherapy resulted in significantly better progression-free survival, overall survival, survival rate, and long-term prognosis versus chemotherapy alone. Moreover, combined therapy was associated with a lower incidence of hemoglobin reduction, gastrointestinal reaction, and renal impairment versus TP regimen chemotherapy (P < 0.05 ). Therefore, we concluded that stereotactic radiotherapy plus chemotherapy with a TP regimen significantly optimizes the clinical efficacy of the NSCLC treatment.